2015
DOI: 10.1007/s10549-015-3508-y
|View full text |Cite
|
Sign up to set email alerts
|

Poly (I: C) modulates the immunosuppressive activity of myeloid-derived suppressor cells in a murine model of breast cancer

Abstract: Polyinosinic-polycytidylic acid [Poly (I: C)], a ligand for Toll-like receptor (TLR-3), is used as an adjuvant to enhance anti-tumor immunity because of its prominent effects on CD8 T cells and NK cells. Myeloid-derived suppressor cells (MDSCs) are one of the main immunosuppressive factors in cancer, and their abnormal accumulation is correlated with the clinical stage of breast cancer and is an important mechanism of tumor immune evasion. Although Poly (I: C) is thought to have direct anti-tumor activity in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 37 publications
0
27
0
1
Order By: Relevance
“…52 Moreover, poly(I:C) abrogated the immunosuppressive functions of myeloid-derived suppressor cells in a murine breast cancer model, leading to an enhanced T cell influx and enhanced survival. 56 Recently, it has been shown that PD-1 on TAMs suppresses their phagocytic functions and antitumor immunity. 57 On the other hand, PD-1 ligand expression by TAMs may contribute to immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…52 Moreover, poly(I:C) abrogated the immunosuppressive functions of myeloid-derived suppressor cells in a murine breast cancer model, leading to an enhanced T cell influx and enhanced survival. 56 Recently, it has been shown that PD-1 on TAMs suppresses their phagocytic functions and antitumor immunity. 57 On the other hand, PD-1 ligand expression by TAMs may contribute to immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors and agents targeting MDSCs have been investigated in recent years. Polyinosinic-polycytidylic acid, a ligand for TLR-3, decreases the number of MDSCs and the immunosuppressive activity in BC by augmenting the T cell response 131. In addition, previous studies have suggested that, in addition to its cytotoxicity against tumor cells, doxorubicin plays a major role in the reduction of MDSC-induced immunosuppression 132…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Pathogen-derived TLR agonists have been shown to induce accumulation of MDSC or to increase their activity 25 , 26 . Some studies, however, have demonstrated differentiation of mature myeloid cells promoting anti-tumor response upon treatment with TLR agonists 27 , 28 . Altogether, the impact of TLR agonists on anti-tumor response seems to be dependent on the cellular context 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%